+0  
 
0
83
1
avatar

Solve for x: (3x + 12)(x + 4) = (4x^2 + 8x + 18x^2)/(2x)

 Jun 26, 2022
 #1
avatar+124676 
+1

 (3x + 12)(x + 4) = (4x^2 + 8x + 18x^2)/(2x)     { assuming that x is  not 0 }

 

3x^2 + 12x + 12x + 48  =  (2x) (2x + 4 + 9x) / (2x)

 

3x^2 + 24x + 48  = 11x + 4

 

3x^2 + 13x + 44  =  0

 

Using the Q formula

 

                     -13 ±√ [ 13^2 - 4 * 3 * 44 ]              13±√ -359           13 ± i√ 359

x =                ______________________  =     _________  =      __________ 

                                    2 *  3                                      6                         6

 

 

cool cool cool

 Jun 26, 2022

8 Online Users